Теоретичні та наукові підходи до визначення сутності та структури потенціалу підприємства - Сукнов, О. М. (ХНУРЕ, 2025)
The study explores theoretical and methodological approaches to assessing enterprise potential in the context of market economy development. It examines the concept of «potential» as a combination of resources, capabilities, and organizational factors influencing business competitiveness. Various interpretations of potential are analyzed, highlighting its role in strategic planning and economic efficiency. The research emphasizes the need for flexible and adaptive management approaches to optimize enterprise potential. The findings contribute to improving assessment methods and enhancing enterprise adaptability in dynamic market conditions.
Keywords: потенціал підприємства; enterprise potential